Migrant families. Intergenerational dynamics and inclusion in socio-educational contexts - Edith Cognigni; Isabella Crespi (University of Bologna, 2022)
The introductory essay frames the monographic section of this volume, which investigates the theme of the family in migration. The research contributions, in presenting various examples of projects and/or interventions implemented in the socio-educational and school contexts in favour of families and children with migrant backgrounds, provide a rich and interesting picture of the main issues regarding families, education and migration. In its own concept, the monographic issue aimed to welcome contributions of both theoretical and applied nature, capable of highlighting innovative and multidisciplinary elements of reflection on these issues, also at the international level.